2012
DOI: 10.1095/biolreprod.111.093161
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Cytometric Isolation and Enrichment of Teleost Type A Spermatogonia Based on Light-Scattering Properties1

Abstract: The transplantation of germ cells is a powerful tool both for studying their development and for reproductive biotechnology. An intraperitoneal germ cell transplantation system was recently developed for use in several teleost species. Donor germ cells transplanted into the peritoneal cavity of hatchlings migrated toward and were incorporated into the recipient's genital ridges, where they underwent gametogenesis. Among male germ cells, only type A spermatogonia were capable of colonizing the recipient gonads,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 27 publications
0
38
1
Order By: Relevance
“…Isolating spermatogonia by flow cytometry using light scatter properties has been reported previously in teleost fish where a cell population highly enriched with undifferentiated type A spermatogonia (∼93% VASA positive) could be obtained from immature rainbow trout testis (Kise et al, ). In the fish study, researchers used a transgenic rainbow trout line that carries a Vasa‐GFP reporter to set a germ cell gate on the light scatter plot and sorted type A spermatogonia from immature non‐transgenic males based on light scatter properties.…”
Section: Discussionmentioning
confidence: 93%
“…Isolating spermatogonia by flow cytometry using light scatter properties has been reported previously in teleost fish where a cell population highly enriched with undifferentiated type A spermatogonia (∼93% VASA positive) could be obtained from immature rainbow trout testis (Kise et al, ). In the fish study, researchers used a transgenic rainbow trout line that carries a Vasa‐GFP reporter to set a germ cell gate on the light scatter plot and sorted type A spermatogonia from immature non‐transgenic males based on light scatter properties.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, methods of isolating and enriching ASGs without the use of transgenic fish are required to apply the germ cell transplantation system to aquaculture and conservation. These methods include FCM isolation based on light‐scattering properties (Ichida et al, ; Kise et al, ), differential plating (Shikina et al, ), Percoll gradient centrifugation (Lacerda, Batlouni, Silva, Homem, & Franca, ; Lacerda et al, ), centrifugal elutriation (Bellaiche et al, ), and a combination of these methods (Lacerda et al, ). We previously reported that FCM dependent on light‐scattering properties makes it possible to isolate and enrich ASGs to 73–93% in several teleosts (Ichida et al, ; Kise et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA probes were synthesized from vasa cDNA fragments of rainbow trout. Probe synthesis and hybridization were performed according to the method described by Kise et al (2012) and Sawatari, Shikina, Takeuchi, and Yoshizaki (2007). A minimum of 100 cells for each specimen was counted to calculate the proportion of vasapositive and vasa-negative cells, and the proportions were expressed as a percentage of total testicular cells.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…2010), which could enable the enrichment of ASG from fish testes using specific antibody‐mediated flow cytometry or magnetic cell sorting. Finally, we recently developed a simple flow cytometry protocol to enrich ASG using light scattering properties (Kise et al. 2012).…”
Section: Discussionmentioning
confidence: 99%